Vipulanandan p–q model to predict the effect of pressurised water on the strengths of gypsum rock in Kurdistan Region, Iraq. Issue 2 (2nd October 2018) - Mohammed, Ahmed; Salih, Nihad
Abstract : In this study, the effects of soaking time and confining water pressure on the compressive and flexural strengths of rock due to the dissolution of gypsum content in rock samples with 96% gypsum (CaSO4 ·2H2 O) content collected from northern Iraq (Kurdistan Region) were investigated. Experiments on compressive strength and flexural strength were performed on gypsum rock samples in normal and pre-saturated conditions. The pre-saturated samples were submerged in distilled water for 35, 70 and 105 d and subjected to confined pressures of 0–0·5 MPa. Thermogravimetric analyses showed a notable reduction in the weight of gypsum rock between 25 and 120°C. Also, the total weight loss at 800°C for the field rock sample was 7·53%. The weight loss of the gypsum rock increased with increasing soaking time and confining water pressure. The gypsum content decreased by 11% under a soaking time of 105 d and a confining water pressure of 0·5 MPa with respect to the natural samples. The compressive strength of the normal gypsum rock was 19·6 MPa, and it decreased by 68 and 90% after 105 d of soaking under confining water pressures of 0 and 0·5 MPa, respectively. The flexural strength of the normal gypsum rock was 10·8 MPa, and it decreased by 65 and 91% after 105 d of soaking under confining water pressures of 0 and 0·5 MPa, respectively. Two non-linear constitutive models were used to simulate the experimental stress–strain relationships in various conditions. The constitutive model parameters were sensitive to the gypsum content. Based on the methods of the coefficients of determination ( R 2 ) and root mean square errors, the non-linear constitutive model (Vipulanandan p – q model) predicted the stress–strain behaviour for the gypsum rock very well.